Intentional vocabulary learning via WhatsApp: Does the type of input matter? - Mojgan Rashtchi; Parisa Yazdani (Universitas Ahmad Dahlan, 2020)
Nowadays, vocabulary as an influential domain in mastering second/foreign languages has encouraged researchers to put forth conceptualizations that can substantiate the successful learning of words. This study used WhatsApp to investigate the different impacts of two input modalities (voice messages vs. written texts) on EFL learners' intentional learning and retention of words. To this end, 50 female EFL learners in two intact classes (n1=n2=25) were selected from a language institute in Khorramabad, Iran. The groups were randomly assigned to two treatment conditions. The results of a general English proficiency test verified their homogeneity at the outset. A standardized teacher-made vocabulary test assured the researchers that the words were unfamiliar to the learners. After the twelve-session treatment, which was integrated with conventional English teaching classes, another standardized vocabulary test was administered once immediately after the intervention and the second time after a two-week interval. The Friedman repeated measures analysis showed a significant difference between the pretest and posttests. However, the results of the statistical analyses showed no statistically significant differences between the participants' performances on the immediate and delayed posttests. Thus, the researchers concluded that the participants had not forgotten the words from the first to the second posttest indicating the efficacy of intentional vocabulary learning. Additionally, no significant differences were found between the two groups showing the similar impacts of the input modality. The study has implications for EFL teachers and educators whose focus is on TEFL.